A closed-loop supply chain considering carbon reduction, quality improvement effort, and return policy under two remanufacturing scenarios. (20th September 2019) - Taleizadeh, Ata Allah; Alizadeh-Basban, Nima; Niaki, Seyed Taghi Akhavan
Abstract: In today's competitive supply chains, providing products which can stimulate the customer's demand and enhance the revenues of companies is an important objective. Therefore, three stimulating factors, including the carbon emission reduction, return policy and quality improvement efforts are taken into consideration in a supply chain (SC). In line with reducing carbon emission, two possibilities in the forward flow, including the technologies investment and the trade and cap are employed. In the reverse flow, hybrid remanufacturing of the imperfect quality products under technology license is investigated. The impacts of collecting-remanufacturing processes on carbon reduction, quality improvement, and SC performance are the key objective of this research. Therefore, two collecting-remanufacturing scenarios, namely A and B, are introduced to analyze the interactions between the abovementioned motivating factors. In Scenario A, the distributor collects the returns paying the refund price, while both the manufacturer and the distributor remanufacture the returns in the hybrid form under a technology license. In Scenario B, however, the third party is added to collect the returns, while the manufacturer and a third party remanufacture the products, where the distributor is only responsible to transfer and sell the products to the customers. The findings illustrate that under all remanufacturing rates investigated, the SC profit under Scenario B is more than that of Scenario A. Moreover, the interactions among the motivating factors are presented, in which a higher refund price has positive effects on the carbon reduction, quality improvement, and SC's profit. Furthermore, employing all of the stimulating factors simultaneously is an effective approach to increase SC performance environmentally and economically. Graphical abstract: Image 106651 Highlights: The effects of some stimulating factors on the performance of a SC are investigated. Quality improvement, return policy, and environmental-friendly production are the factors. A technology licensing policy is used to remanufacture returned products. Two channels (A and B) are considered to remanufacture the returned products. Supply chain's profit under Scenario B is more than that of Scenario A.